PENEGAKAN HUKUM PIDANA TERHADAP PELAKU TINDAK PIDANA TURUT SERTA PENCURIAN DALAM KEADAAN MEMBERATKAN YANG DILAKUKAN WANITA DI MALL BOEMI KEDATON : Zainab ompu zainah1, Via Fristha Dewi2, - ompu zainah, Zainab; Viafristhadew (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2024)
Abstract The brief definition of a thief is someone who commits acts of theft. The definition of thief in the legal dictionary is not written and explained clearly, but the legal dictionary explains the meaning of the word theft, namely taking someone else's property without permission or in an illegal way with the intention of possessing it unlawfully. Research methods used in this thesis research namely the normative juridical approach and the empirical approach. Criminal liability for perpetrators of criminal acts involving theft in aggravating circumstances committed by women based on Decision Number: 525/Pid.B/2020/Pn.Tjk, The defendants were legally and convincingly proven to have violated the provisions of Article 363 paragraph 1-4 of the Criminal Code Thus, the Panel of Judges handed down a sentence of imprisonment for 1 year. The basis for the judge's considerations in handing down a verdict against the perpetrator of the crime of theft in aggravating circumstances committed by a woman in Decision Number: 525/Pid.B/2020/Pn.Tjk was the defendant M and his colleagues. his partner had fulfilled the elements in Article 363 paragraph (1) 4th, apart from that the Panel of Judges also based on the aggravating circumstances, namely the defendant's actions were detrimental to PT Candra Sekawan Abadi and the defendant's actions disturbed the community, as well as mitigating circumstances the defendant was polite in court and the defendant admitted guilt and regret for his actions.